Geotechnical aspects of underground construction in soft ground : proceedings of the 5th International Symposium of TC28 of the ISSMGE, the Netherlands, 15-17 June 2005 /: proceedings of the 5th International Symposium of TC28 of the ISSMGE, the Netherlands, 15-17 June 2005. (2006) - Unknown
No abstract available